Configural Cues Associated with Reward Elicit Theta Oscillations of Rat Retrosplenial Cortical Neurons Phase-Locked to LFP Theta Cycles. (8th January 2021) - Yoshida, Masashi; Chinzorig, Choijiljav; Matsumoto, Jumpei; Nishimaru, Hiroshi; Ono, Taketoshi; Yamazaki, Mitsuaki; Nishijo, Hisao
Abstract: Previous behavioral studies implicated the retrosplenial cortex (RSC) in stimulus–stimulus associations, and also in the retrieval of remote associative memory based on EEG theta oscillations. However, neural mechanisms involved in the retrieval of stored information of such associations and memory in the RSC remain unclear. To investigate the neural mechanisms underlying these processes, RSC neurons and local field potentials (LFPs) were simultaneously recorded from well-trained rats performing a cue-reward association task. In the task, simultaneous presentation of two multimodal conditioned stimuli (configural CSs) predicted a reward outcome opposite to that associated with the individual presentation of each elemental CS. Here, we show neurophysiological evidence that the RSC is involved in stimulus–stimulus association where configural CSs are discriminated from each elementary CS that is a constituent of the configural CSs, and that memory retrieval of rewarding CSs is associated with theta oscillation of RSC neurons during CS presentation, which is phase-locked to LFP theta cycles. The results suggest that cue (elementary and configural CSs)-reinforcement associations are stored in the RSC neural circuits, and are retrieved in synchronization with LFP theta rhythm.